Adolescents in contemporary Indonesia - Parker, Lyn; Nilan, Pam (Milton Park : Routledge, 2013)
'The youth demographic is a large and growing cohort in Indonesia, and adolescents embody the currents of social change. Throughout the twentieth century they were significant agents of social protest leading to social and political transformation. This book looks at the important of adolescents in contemporary Indonesia, and how they are spearheading not just globalisation and a growing consumer youth culture, but also the Islamisation movement. The book explores both the inner worlds and social selves of Indonesian adolescents. It presents an in-depth knowledge of Indonesian society and culture in various parts of Indonesia, and discusses national patterns and trends. Grounded in two field sites, the book enables an analysis of young people's local ethnic and religious identities and their commitment to the Indonesian nation-state. It goes on to look at the physical age bracket of youth, the definitions used by the Indonesian state and other agencies, and the perceptions of youth themselves about adolescence and adulthood. Providing a comprehensive study of young people in contemporary Indonesia, the book addresses gender relations, the importance of education for youth and youth engagement with popular culture, and the moral issue concerning the sexual propriety of young people'--Provided by publisher.
Introducing Indonesian youth -- From pemuda to remaja -- The worlds of young people in Solo, Central Java -- The moral world of Minangkabau adolescents in West Sumatra -- The meaning of education for young people -- Free seks, moral panic and the construction of the moral self -- Leisure and socializing : maintaining the moral self in gendered leisure -- The hopes and dreams of young people.
Includes bibliographical references and index.
Keywords: Young adults -- Indonesia; Teenagers -- Indonesia; Youth -- Indonesia